Magnesium pentahydridocobalt(I) strontium hydride - Noréus, D. (My University, 2016)
Inelastic Neutron Scattering spectrum of Magnesium pentahydridocobalt(I) strontium hydride, SrH2Mg2[CoH5], measured on the TOSCA instrument.
Keywords: TOSCA